An updated list of the type specimens of Caelifera (Orthoptera) in the Museu Nacional, Rio de Janeiro - Monné, Miguel A. (Zootaxa, 2018)
A checklist of the type specimens of 273 species of Caelifera (Orthoptera) deposited in the Museu Nacional, Universidade de Rio de Janeiro (MNRJ), Rio de Janeiro, Brazil is provided.